Analyzing Business Leadership Skills Under Uncertain Environment Using Fuzzy AHP Approach. - NGUYEN, PHI-HUNG (The journal of contemporary issues in business and government, 2021)
Over the years, leaders affect followers’ success and inspiration. Up to this point, research has concentrated on leader characteristics, attitudes, or followers’ self-concepts and the related consequences. Dynamic leadership attracts attention because it leads to promoting future business leadership. This study aims to analyze the influencing factors of business leadership. This study proposes the Fuzzy Analytical Hierarchy Process Method (FAHP) to achieve a systematic weighting of critical factors affecting business leadership to overcome human expectations’ vagueness. Group of critical criteria basing on experts’ opinions are identified: Creative Thinking (A), Cause-Effect Analysis (B), Forecasting (C), Planning (D), Visioning (E), Problem Defining (F), Idea Evaluation (G), Wisdom (H), and Constraint Analysis (I). The results revealed that Visioning (E) is the most critical skill at a weight of 0.138, Forecasting (C) is the second position and Creative Thinking (A) is placed third with the weight of 0.126. The remaining skills’ rankings are Cause-Effect Analysis (B) > Planning (D)> Idea Evaluation (G)>Wisdom (H) Constraint Analysis (I)> Problem Defining(F), respectively. The implications of findings bearing on leader thinking skills for leader assessment and leader development are considered. Finally, sensitivity analysis is conducted to verify the robustness of the results.